2009
DOI: 10.3390/v1031166
|View full text |Cite
|
Sign up to set email alerts
|

Complete Nucleotide Analysis of the Structural Genome of the Infectious Bronchitis Virus Strain Md27 Reveals its Mosaic Nature

Abstract: Infectious bronchitis virus (IBV) causes highly contagious respiratory or urogenital tract diseases in chickens. The Maryland 27(Md27) strain was first isolated in 1976 from diseased chicken flocks in the Delmarva Peninsula region. To understand the genetic diversity and phylogenetic relationship of existing strains with Md27, the complete nucleotide sequence of the 3′end coding region (∼7.2 kb) of Md27 was determined and compared with other IBV strains and coronaviruses. It has the same S-3-M-5-N-3′ gene orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
2
7
1
Order By: Relevance
“…The insertions of aspartic acid, glycine and serine in the sequences of the isolates may affect antigenicity of the virus, and this will be a question for further studies on serotyping of the isolates. Our results are consistent to those were obtained by previous studies (Ammayappan and Vakharia, 2009;Liu et al, 2009).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The insertions of aspartic acid, glycine and serine in the sequences of the isolates may affect antigenicity of the virus, and this will be a question for further studies on serotyping of the isolates. Our results are consistent to those were obtained by previous studies (Ammayappan and Vakharia, 2009;Liu et al, 2009).…”
Section: Discussionsupporting
confidence: 94%
“…Previously it has been reported that Ark-like strains have a deletion of three nucleotides in the S1 gene at nucleotides positions 69-71 (Ammayappan and Vakharia, 2009) but in this context, we have observed insertion rather than deletion in S1 unit of the sequences of D388/ QX-like strains. These insertions and deletions possibly have some significance in the properties related to S1 functions.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…The assembly of contiguous sequences of ck/CH/LGX/130530, tl/CH/LDT3/03 and LDT3-A was performed with GeneDoc software (Ammayappan and Vakharia, 2009). Both the S1 gene and complete genomic sequences of IBV isolate ck/CH/LGX/130530 were used for BLAST searching of the National Center for Biotechnology Information (NCBI) database.…”
Section: Sequence Analysismentioning
confidence: 99%